MANIFESTASI KLINIS DAN DIAGNOSIS MIGREN VESTIBULAR - Sitorus, Freddy; Rida Ariarini, Ni Nengah; Tunjungsari, Dyah (Majalah Kedokteran Neurosains Perhimpunan Dokter Spesialis Saraf Indonesia, 2018)
CLINICAL MANIFESTATION AND DIAGNOSIS OF VESTIBULAR MIGRAINEABSTRACTVestibular migraine (VM) is the most common cause of recurrent spontaneous vertigo on outpatient dizziness clinics. Clinical manifestation of VM is highly variable. Patient may present symptoms like vertigo, dizziness, tinnitus, visual disturbance, phonophobia, photophobia, aural fullness, paresthesia, nausea, and vomiting. Most VM patients have normal physical examination between attacks. Diagnostic criteria of this disease based on joint consensus of the International Headache Society (IHS) together the Barany Society published in 2012. The Differential diagnosis of this disease are benign paroxysmal positional vertigo (BPPV), Meniere’s disease, and acute ischemic attack. Moreover, vestibular migraine treatment is almost the same as for migraine.Keywords: Clinical manifestation, diagnosis, vestibular migraineABSTRAKMigren vestibular (MV) merupakan penyebab tersering vertigo spontan berulang pada pasien di poliklinik spesialis yang menangani rasa goyang. Manifestasi klinis dari migren vestibular sangat bervariasi. Pasien dapat mengeluhkan gejala seperti vertigo, pusing, tinitus, gangguan penglihatan, fonofobia, fotofobia, aural fullness, parestesi, mual, dan muntah. Pemeriksaan fisik pada pasien MV biasanya normal di antara serangan. Penegakan diagnosis penyakit ini berdasarkan konsensus bersama antara International Headache Society (IHS) dan Barany Society pada tahun 2012. Diagnosis diferensial penyakit ini adalah benign paroxysmal positional vertigo (BPPV), penyakit Meniere, dan serangan iskemik akut. Sampai saat ini, terapi untuk migren vestibular hampir sama dengan terapi migren pada umumnya.Kata kunci: Diagnosis, manifestasi klinis, migren vestibular